The Urgency of Health Insurance Literacy for Indonesian People: Between Smoking and Paying JKN Premium - Sitohang, Marya Yenita; Ghani, Mochammad Wahyu (Faculty of Public Health, Universitas Diponegoro, Semarang, Indonesia, 2022)
Introduction: Declining the rates of smoking among the poor still becomes a challenge for the health sector. Ideally, they can use the money for smoking to pay for their family health insurance premium. This research aimed to analyze how the poor in the informal sector perceived the payment of National Health Insurance (NHI/ JKN) using the cigarette cost.Methods: Data were collected from focus group discussions (FGD) in three different locations, Deli Serdang, Sumedang Districts and Medan City. Thirty-three informal sector workers with low financial capabilities participated in these FGDs. Health Belief Model was used as the framework for analyzing the data and information. Data analysis was conducted through the content analysis method.Results: The finding showed that poor people who work in the informal sector gave two different responses regarding the use of cigarette costs for paying the NHI/JKN program premium. The respondents had already an excellent perceived susceptibility and severity both on smoking habits and their low finance condition. They believed that the NHI/JKN benefit was to protect them financially if their family members need medical treatment. However, they had low self-efficacy and high perceived barriers that hinder them from replacing the money for buying cigarettes into paying for NHI/JKN premium.Conclusion: An approach to the poor people in the informal sector within their local context, is urgently needed to increase their health insurance literacy and knowledge about smoking.